Collecting the New : Museums and Contemporary Art - Altshuler, Bruce (Book collections on Project MUSE., 2005)
Collecting the New is the first book on the questions and challenges that museums face in acquiring and preserving contemporary art. Because such art has not yet withstood the test of time, it defies the traditional understanding of the art museum as an institution that collects and displays works of long-established aesthetic and historical value. By acquiring such art, museums gamble on the future. In addition, new technologies and alternative conceptions of the artwork have created special problems of conservation, while social, political, and aesthetic changes have generated new.